Tinjauan Hukum Islam terhadap Jual Beli Makanan Sistem Al-Qard di Kantin Sirin Sinhan Kabupaten Sambas - Azmi; Juniarti (CV Global Research Publication, 2025)
Buying and selling is an exchange transaction that must fulfill the principles of lawfulness, fairness, and contractual clarity in Islam. However, the food trading practice in Sirin Sinhan Canteen, Sambas Regency, presents a different phenomenon, where payments are made on a deferred basis and charged to the government budget through administrative receipts, resulting in discrepancies in transaction values. This condition raises questions regarding the compliance of such practices with Islamic legal provisions. This study employs a qualitative approach with a non-doctrinal (empirical) legal research method to examine the transaction practices and payment mechanisms at the canteen. The findings reveal that the transaction is not a cash sale, but rather an al-qard (loan-based) contract due to delayed payments by customers, mostly civil servants. Moreover, inconsistencies in debt amounts between the canteen receipts and government documents indicate potential contractual uncertainty. Therefore, improvements in the payment system are required to ensure conformity with Sharia principles and uphold fairness for both parties.